Drug-induced eosinophilic pneumonia: A review of 196 case reports. Issue 4 (January 2018) - Bartal, Carmi; Sagy, Iftach; Barski, Leonid
Abstract: Background and objective: Eosinophilic pneumonia (EP) is an important subset of patients who present with pulmonary infiltrates and eosinophilia (PIE). EP is classified by chronicity and etiology and drug-induced EP is the main cause of secondary EP. The primary goal of this review was to examine all the case reports published since the syndrome was defined in 1990. It remains unclear whether acute or chronic EP (AEP or CEP) represent different diseases, and the secondary goal of this review is to determine if there are factors that may help distinguish these 2 entities. Methods: PubMed (MEDLINE and Medical Subject Headings) was searched for case reports of drug-induced EP or PIE syndrome published between 1990 and 2017. Case reports were only included if the diagnostic criteria for AEP or CEP were fulfilled. For each case, data were extracted pertaining to age, sex, type of medication associated with the disease, time from the onset of symptoms to diagnosis, eosinophil counts in the blood, eosinophil fractions in bronchoalveolar lavage (BAL) fluid, initial chest radiograph and computed tomography results, use of mechanical ventilation, and use of steroid treatment and recurrence. Results: We found 196 case reports describing drug-induced EP. The leading cause was daptomycin. From our review, we found that AEP is more common in younger patients with no gender preference. Eosinophilia in the blood at the time of diagnosis characterized only the CEP patients (80% in CEP vs. 20% in AEP). Abnormal findings on radiographic imagine was similar in both syndromes. A significant portion of AEP patients (20%) presented with acute respiratory failure requiring mechanical ventilation. Most patients with EP were treated with steroids with a higher rate of relapse observed in patients with CEP. Conclusion: AEP is a much more fulminant and severe disease than the gradual onset and slowly progressive nature of CEP. The pathogenesis of AEP and CEP remains unclear. However, there is significant clinical overlap among AEP and CEP that are associated with drug toxicity, suggesting the possibility that AEP and CEP are distinct clinical presentations that share a common pathogenic pathway.